On Certain Multivalent Functions - Mamoru Nunokawa; Shigeyoshi Owa; Tadayuki Sekine; Rikuo Yamakawa; Hitoshi Saitoh; Junichi Nishiwaki (International Journal of Mathematics and Mathematical Sciences)
Let 𝒮*(p,α) be the class of functions f(z) which are analytic and p-valently starlike of order α in the open unit disk E. The object of the present paper is to derive an interesting condition for f(z) to be in the class 𝒮*(p,α).